ANALISIS RESPON PENAWARAN PETANI KENTANG DI KECAMATAN JANGKAT KABUPATEN MERANGIN - Edison, .; Denmar, Denny (Indonesian Journal of Socio Economics)
In Otonomi Daerah (OTDA) era, Regional government efforts to look for regional potency in order to increase Pendapatan Asli Daerah (PAD). Potato in Merangin Regency has given a significant contribution in Meranginâs PDRB. Supply response and input demand by potatoesâ farmers in Jangkat District Merangin Regency was estimated by using profit function. The objective of this study is to analyze supply response on potatoesâ farmers. Research was conducted in three villages, Kayu Aro Jangkat district Merangin Regency in 2005. The result showed that farmers do maximize their profit in short term and response to price changing efficiently. Potatoâs supply elasticity with considering its price was closed to one.